Improving Students' Grammar Mastery through Classroom Based Online Game - Saka Ilham Haqiqi; Yahya Alaydrus; Dzurriyyatun Ni'mah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2019)
Facing students’ difficulties in grammar acquisition, different teaching technique is introduced. Classroom based online game is one of the technique that can be used to improve students’ grammar mastery issue. This techique is an instructional activity that uses online platform for learning games which can be utilized to introduce, test and revise variety of material including language lesson. The objective of this study was to find out whether the use of classroom based online game technique in teaching English could improve grammar mastery of the first semester students of English Department, University of Islam Malang. The research design of the study was classroom action research (CAR) which was conducted in one cycle consisting of four meetings. The subject of this study were 25 first semester students of English Department. In this study, the researcher used some instruments; those were: field note to take the information of the students’ activities in the classroom and grammar test to know the students’ achievement. The findings indicated that the application of this technique improved the students’ grammar mastery. It was proven that 76% of students got the score above the minimal mastery level criterion. It was higher than the preliminary study that only 24% of students achieved the minimal mastery level criterion.